Investigación en Medicina Clínica Research in Clinical Medicine - Alvar Agustí (Educación Médica, 2004)
Este artículo presenta una visión personal sobre la investigación clínica. La información presentada no está basada en la evidencia. Por tanto, todas las opiniones vertidas son discutibles y, probablemente, erróneas. En primer lugar discute qué debe entenderse por investigación clínica y el porque de su relevancia, no sólo intrínseca (per se) sino también aquella derivada de una serie de "efectos colaterales" que, a juicio del autor son importantes en el ámbito del sistema nacional de salud y no son siempre apreciados o valorados. En la segunda parte del artículo se proponen una serie de "requisitos" para poder realizar investigación clínica y se anticipa (si es que ello es posible) cual será el futuro (posiblemente ya el presente) de la investigación clínica que, de nuevo a juicio del autor, pasa ineludiblemente por la multi-disciplinariedad y la multi-centricidad. De ahí, la importancia estratégica de los diversos proyectos de investigación "en red" propuestos tanto a nivel nacional (www.retics.net) como europeo (VI Programa Marco) o norte-americano (National Institutes of Health). This article presents a very personal view of clinical research. It is not evidence based. Thus, all the opinions included are arguable and even likely to be incorrect. It first discusses what is clinical research. Then, it highlights the reasons underlying the key importance of clinical research within the broader field of biomedical research. Some of these reasons are self-evident whereas others are often missed or ignored in the context of the public health systems. In the last part of the paper, the type and extent of knowledge required by someone interested in developing a career in clinical research is also discussed. Finally, the "future" of clinical research is anticipated, although it is recognized that this future is already here (at least its beginning). It is the opinion of the author that future clinical research will be based upon two fundamental aspects: the collaboration between different scientific disciplines and the need of having different groups of investigators participating in the research project. It is in this context where the strategic importance of the new "research networks" promoted by both the European Union (VI Framework Programme) and the USA (National Institutes of Health) can be fully appreciated. In our country, this vision has been promoted by the Instituto de Salud Carlos III (specific information can be found at www.retics.net).